Finite-Time Stabilization of Stochastic Nonholonomic Systems and Its Application to Mobile Robot. (30th October 2012) - Gao, Fangzheng; Yuan, Fushun
Abstract : This paper investigates the problem of finite-time stabilization for a class of stochastic nonholonomic systems in chained form. By using stochastic finite-time stability theorem and the method of adding a power integrator, a recursive controller design procedure in the stochastic setting is developed. Based on switching strategy to overcome the uncontrollability problem associated with x 0 ( 0 ) = 0, global stochastic finite-time regulation of the closed-loop system states is achieved. The proposed scheme can be applied to the finite-time control of nonholonomic mobile robot subject to stochastic disturbances. The simulation results demonstrate the validity of the presented algorithm.